Prediction of foveal microstructure and visual outcomes following surgery for idiopathic macular hole: An assessment using spectral-domain optical coherence tomography - Qintuo Pan; Jingwei Zheng; Zhaoliang Zhang; Zongduan Zhang; Xuting Hu (Indian Journal of Ophthalmology, 2024)
Purpose: To evaluate the efficacy of two novel indices, the hole closure index (HCI) and the hole healing index (HHI), in predicting both the anatomic outcome and postoperative visual acuity following surgical intervention for idiopathic macular holes. Methods: A total of 38 patients diagnosed with idiopathic macular hole (IMH) were included. All patients underwent standard surgical treatment, including vitrectomy, internal limiting membrane (ILM) peeling, and gas tamponade. Preoperative and postoperative spectral-domain optical coherence tomography (SD-OCT) was utilized to assess the anatomical status of the macular hole (MH). The maximum distance between the tips of the external limiting membrane (ELM) was designated as the hole size (HS). HHI, calculated as the ratio of hole height to HS, and HCI, calculated as the ratio of hole height to the average of minimum diameter and base diameter, were determined. Postoperative reconstruction of ELM and ellipsoid zone (EZ) was evaluated, along with analysis of best-corrected visual acuity (BCVA) on a logarithm of the minimum angle of resolution (logMAR) scale. Regression analysis was performed to evaluate the relationship between anatomical outcomes, postoperative visual acuity, and optical coherence tomography (OCT) parameters. Receiver operating characteristic (ROC) curves were generated for both HHI and HCI. Results: Regression analyses revealed significant correlations between HCI and the restoration of ELM and EZ at 6 months after surgery (P = 0.002 and P = 0.014, respectively). In addition, a significant correlation was found between HHI and postoperative BCVA better than logMAR 0.52 also at 6 months after surgery (P = 0.033). The area under the ROC curve (AUC) for HCI based on ELM and EZ reconstruction was high, with values of 0.942 and 0.842, respectively. AUC for HHI, determined by ROC curve analysis of postoperative BCVA, was 0.704. Conclusions: In conclusion, our findings indicate that HCI may be the most accurate predictor of type 1 closure, while HHI could be considered a potential predictor of postoperative visual acuity.